Organizational compassion a relational approach - Simpson, Ace Volkmann; Cunha, Miguel Pina e 1965-; Clegg, Stewart 1947-; Rego, Arménio ca. 20.-21. Jh; Berti, Marco 1965- (Routledge, 2024)
This important book provides an accessible yet scholarly overview of key academic findings and theories on organizational compassion.